2010
DOI: 10.1186/1532-429x-12-50
|View full text |Cite
|
Sign up to set email alerts
|

Nasal continuous positive airway pressure improves myocardial perfusion reserve and endothelial-dependent vasodilation in patients with obstructive sleep apnea

Abstract: BackgroundObstructive sleep apnea (OSA) has been associated with cardiovascular disease (CVD), but whether OSA is an independent risk factor for CVD is controversial. The purpose of this study is to determine if patients with OSA have subclinical cardiovascular disease that is detectable by multi-modality cardiovascular imaging and whether these abnormalities improve after nasal continuous positive airway pressure (nCPAP).ResultsOf the 35 consecutive subjects with newly diagnosed moderate to severe OSA recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 35 publications
1
48
0
Order By: Relevance
“…One small study with CPAP randomization using cardiac magnetic resonance to estimate MBFR demonstrated similar results in coronary perfusion after CPAP treatment. 41 Another limitation of our study is that, despite using strict inclusion and exclusion criteria, the mean systolic BP in the OSA group was 141 mm Hg. Therefore, the possibility of masked hypertension cannot be excluded altogether, especially because we did not have 24-hour ambulatory BP recordings in this group.…”
Section: Limitationsmentioning
confidence: 89%
“…One small study with CPAP randomization using cardiac magnetic resonance to estimate MBFR demonstrated similar results in coronary perfusion after CPAP treatment. 41 Another limitation of our study is that, despite using strict inclusion and exclusion criteria, the mean systolic BP in the OSA group was 141 mm Hg. Therefore, the possibility of masked hypertension cannot be excluded altogether, especially because we did not have 24-hour ambulatory BP recordings in this group.…”
Section: Limitationsmentioning
confidence: 89%
“…In a recent randomized controlled trial, 24 weeks of CPAP treatment alone (on average z4 h per night) did not improve insulin sensitivity as assessed by ivGTT (27). Previous randomized controlled trials have found no benefit of CPAP treatment on measures of glucose metabolism when the duration of average CPAP use ranged from 3.3 to 6.2 hours per night (20)(21)(22)(23)(24)(25)(26)(27)(28). In one controlled study involving individuals with prediabetes, 2 months of CPAP use (on average z4.8 h per night) led to an improvement in insulin sensitivity only in those who had severe OSA (29).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this strong association between OSA and alterations in glucose metabolism, there is still controversy as to whether treatment of OSA with continuous positive airway pressure (CPAP) has metabolic benefits (18,19). Prior randomized controlled trials investigating the effects of CPAP on measures of glucose metabolism yielded mostly negative results (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The average duration of CPAP use in these trials ranged from 3.3 to 6.2 hours per night.…”
mentioning
confidence: 99%
“…Numerous studies have also explored the effects of CPAP on FMD as a surrogate vascular outcome. [10][11][12][13][14][15][16][17][18][19][20] Although these studies demonstrated the favorable effect of CPAP on endothelial function, confounding factors such as obesity, insulin resistance, and metabolic syndrome, all of which influence endothelial function, must also be taken into account. In this review, we sought to retrieve all published studies on the effects of CPAP on FMD and NMD in subjects with OSA and to quantify the potential contribution of CPAP to improving endothelial function.…”
Section: Introductionmentioning
confidence: 99%